Studi Perubahan Sosial Peserta Didik Akibat Teknologi Informasi - Reisya Namira; Munali Munali; Moch. Apip (ALSYS, 2026)
Advances in modernization and information technology have brought significant changes to social, cultural, and educational life, particularly as learning is no longer confined to formal institutions but is increasingly supported by broad access to learning resources through the internet and digital media. This condition requires society to use technology wisely and in accordance with digital ethics. This study aimed to analyze social changes resulting from information technology across three dimensions: changes in interaction patterns, community adaptation to digitalization, and the emergence of new social phenomena. The study employed a mixed-methods approach involving 70 respondents consisting of school students, university students, and members of the school community selected through convenience sampling. Data were collected over one month using a 15-item questionnaire with yes/no response options distributed via Google Forms and interviews, and were then analyzed using percentage analysis. The results showed an average score of 91%, which fell into the very good category, although relatively lower scores were found for face-to-face interaction (83%), digital adaptation (86%), and the influencer phenomenon (87%) compared with the other aspects. These findings confirm that information technology drives broad social change, while simultaneously requiring stronger digital literacy and a balance between digital interaction and face-to-face interaction in everyday life.